Extraction of Starfish Bioactive Compounds (Protoreaster nodosus) from Army Dock Water Morotai Island Regency - Yungleit Masa; Nurafni Nurafni; Rinto Muhammad Nur (Faculty of Agriculture Musamus University, 2021)
Starfish are included in the class asteroidea, and are grouped into the Phylum Echinoderms. Starfish can be used by humans both as food, decoration and commodities for export. The purpose of this study was to determine the yield of starfish extract (Protoreaster nodosus) and identify the types of bioactive compounds contained in the methanol extract of Protoreaster nodosus from Army Dock Waters, Views Village, Morotai Island Regency. This research was conducted in December 2019-January 2020. It started with taking samples of starfish (Protoreaster nodosus) from Army Dock Waters, Morotai Island Regency. Sample analysis was carried out at the FPIK Laboratory of the Pacific Morotai University. Sample extraction using methanol maceration with methanol solvent. Identification of groups of bioactive compounds include alkaloids, flavonoids, steroids/triterpenoids, saponins, quinones, and phenols. The research data obtained were then analyzed descriptively. Results the starfish extract obtained has a paste like texture, reddish yellow in color and has clear granules like crystals. The yield of methanol extract was 2.15 % and Identification of the class of bioactive compounds in the starfish (Protoreaster nodosus) contains bioactive compounds of alkaloids, steroids, and flavonoids.